The impact of orthodontic treatment on normative need. A case-control study in Peru - Bernabé Eduardo; Borges-Yáñez Socorro A.; Flores-Mir Carlos (Sciendo, 2023)
To assess the impact of previously provided orthodontic treatment on the normative need in a sample of young adult Peruvians.